Design, Charecterization of Imidapril Mouth Dissolving Tablets Using Super Disintegrants - Ismail Y.; V. Vijaya Kumar (Advanced Concepts in Pharmaceutical Research Vol. 4, 2024)
Objective: The aim of this study was preparing once daily mouth disintegrating tablets to handle easily for adult hypertensive patients who have difficulty in swallowing. Background: The oral bioavailability of Imidapril can be enhanced by decreasing its extent of first pass effect. Mouth dissolving tablet formulation has been widely and successfully applied to improve the dissolution, solubility, and consequently the bioavailability of poorly water-soluble drugs. Methods: Imidapril mouth dissolving tablets (MDTs) were prepared by direct compression method using different concentrations of synthetic super disintegrants namely Sodium starch glycolate, Croscarmellose sodium & Kyron T-314. The prepared tablets were evaluated for weight variation, thickness, hardness, friability, content uniformity, disintegration time and In-vitro dissolution studies. Results: The micropolitics study indicates that all formulations were of acceptable to good flowability. Tablet hardness and friability indicated that the prepared formulations were having good mechanical strength. The most satisfactory formulation F5 containing Sodium starch glycolate showed minimum disintegration time of 19 s and released a maximum amount of drug in 30 min in phosphate buffer 6.8pH, by an appropriate combination of excipients. The optimized F5 formulation containing Sodium starch glycolate was found to be stable during stability studies conducted for 3 mo as per International Conference on Harmonization (ICH) guidelines. The dissolution rate was found to be increased linearly with increase in the concentration of super disintegrant. The investigated super disintegrants can be ranked based on the overall in-vitro release profile of Imidapril Mouth dissolving tablet i.e. Sodium starch glycolate>Kyron T314>Croscarmellose sodium. Conclusion: The present study conclusively proved that Imidapril MDTs could be successfully developed using various super disintegrants. The prepared tablets gave promising results with respect to the faster release of Imidapril. Further clinical studies are suggested to confirm the ability of the best-achieved system to avoid the first pass metabolism of Imidapril and improve patient compliance.